Methodological Insights into Cancer Driver Gene Prediction: Comparing Graph-Based and Traditional ML Approaches - Andrades, Renan Soares de; Recamonde Mendoza, Mariana (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
This study investigates the impact of key methodological choices on cancer driver gene (CDG) prediction using graph neural networks (GNNs) and traditional machine learning (ML) models. We evaluate three GNN architectures, four ML algorithms, three protein–protein interaction networks, multiple node feature configurations (single-omics, multi-omics, centrality measures), and three strategies to mitigate class imbalance. Graph Convolutional Networks consistently outperform other GNNs, while Gradient Boosted Trees remain competitive when structural features are included. Node centrality measures further enhance prediction across models. These results underscore the role of feature design and model selection in achieving accurate and robust CDG prediction.